Time delays, competitive interdependence, and firm performance. (20th April 2016) - Luoma, Jukka; Ruutu, Sampsa; King, Adelaide Wilcox; Tikkanen, Henrikki
Abstract : Research summary: Competitors' experiences of prior interactions shape patterns of rivalry over time. However, mechanisms that influence learning from competitive experience remain largely unexamined. We develop a computational model of dyadic rivalry to examine how time delays in competitors' feedback influence their learning. Time delays are inevitable because the process of executing competitive moves takes time, and the market's responses unfold gradually. We analyze how these lags impact learning and, subsequently, firms' competitive behavior, industry profits, and performance heterogeneity. In line with the extant learning literature, our findings reveal that time delays hinder learning from experience. However, this counterintuitively increases rivals' profits by reducing their investments in costly head‐to‐head competition. Time delays also engender performance heterogeneity by causing rivals' paths of competitive behavior to diverge . Managerial summary: While competitive actions such as new product launches, geographical expansion, and marketing campaigns require up‐front resource commitments, the potential lift in profits takes time to materialize. This time delay, combined with uncertainty surrounding the outcomes of competitive actions, makes it difficult for managers to learn reliably from previous investment decisions. This results in systematic underinvestment in competitive actions. The severity of the underinvestment grows as the time delay between an investment and its positive results increases. Counterintuitively, however, competitors' collective underinvestment increases profit‐making opportunities. In industries with large time delays, companies that do invest in competitive actions are likely to enjoy high returns on investment. It is also likely that rivals' paths of competitive behavior bifurcate. Together, these mechanisms generate large differences in competitors' profits . Copyright © 2016 John Wiley & Sons, Ltd.